ROLE OF ERANDA TAILA (CASTOR OIL) IN SUKH-PRASAVA: CASE REPORTS - Jain, Anjali; Pushpalatha, B; K, Bharathi (International journal of research in ayurveda and pharmacy, 2025)
Great things can be achieved only with labor. To attain the unlimited happiness of motherhood also, labor is very much essential. But the labor should be natural and bearable. When, the fetus is expelled out through vagina with less duration and intensity of pain to mother, it is called as Sukha Prasava. The opinions of Acharyas regarding the onset of labor vary with each other; still, all the opinions coincide to conclude that in between 9 and 12 months, the labor should take place. Total two cases were observed, one involving a primigravida and the other was a second gravida with gestational age between 40 to 41 weeks visited the OPD of Prasuti and Stree Roga, National Institute of Ayurveda, Jaipur, India, after per vaginal examination advised for admission and planned for orally intake of Eranda Taila. All the two subjects delivered vaginally without any complications to babies with average weight 2800 grams. Their postnatal period was uneventful. An ayurvedic formulation which is cost effective, easily available can be very well-made use for the induction of labor. In all these cases, no chemical drugs used to induce or augment the labor.